2003
DOI: 10.1089/108729103322277420
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Mental Health and Psychosocial Predictors of Medical Treatment Adherence in Mothers Living with HIV Disease

Abstract: Cross-sectional studies to date that examine psychosocial correlates of antiretroviral adherence have insufficiently addressed the challenges of long-term adherence. This longitudinal study examined mental health, substance abuse, and psychosocial predictors of long-term adherence to antiretroviral medications and medical appointments among HIV-seropositive mothers recruited from an infectious disease clinic of a large urban medical center. Individual interviews were conducted at baseline and two follow-up poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
110
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 43 publications
5
110
0
Order By: Relevance
“…Pre-existing psychological and psychiatric disorders can become aggravated with a diagnosis of HIV, or may develop during the course of living with HIV/AIDS (Mellins, Kang, Leu, Havens, & Chesney, 2003). The most common are mood disorders, such as depression, dysthymia, mania and, anxiety disorders, such as generalized anxiety, panic and post-traumatic stress (Mellins et al, 2003;Golub et al, 2003;Cook et al, 2004;Hamer, 2000;Sikkema, 2003).…”
Section: Hiv/aids and Mental Illnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre-existing psychological and psychiatric disorders can become aggravated with a diagnosis of HIV, or may develop during the course of living with HIV/AIDS (Mellins, Kang, Leu, Havens, & Chesney, 2003). The most common are mood disorders, such as depression, dysthymia, mania and, anxiety disorders, such as generalized anxiety, panic and post-traumatic stress (Mellins et al, 2003;Golub et al, 2003;Cook et al, 2004;Hamer, 2000;Sikkema, 2003).…”
Section: Hiv/aids and Mental Illnessmentioning
confidence: 99%
“…The most common are mood disorders, such as depression, dysthymia, mania and, anxiety disorders, such as generalized anxiety, panic and post-traumatic stress (Mellins et al, 2003;Golub et al, 2003;Cook et al, 2004;Hamer, 2000;Sikkema, 2003). HIV/AIDS disease progression can impact neurological and neurocognitive status.…”
Section: Hiv/aids and Mental Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study with HIV-positive mothers found that experience of acute stressful life events was associated with missed pills and appointments at follow-up. 22 The present study investigated the role of both aspects of stress on treatment adherence among HIV-positive adults.…”
Section: Introduction Tmentioning
confidence: 99%
“…A variety of factors was reported regarding nonadherence to medication in patients with HIV such as substance abuse (8)(9)(10)(11)(12), health beliefs (13-15), psychiatric status (12,(16)(17)(18)(19)(20)(21), demographic characteristics (10,20), social factors (22), familial factors (23)(24)(25), medication side effects (17,26), and cognitive functioning (10,14,26). Although previous studies drawn a comprehensive picture of barriers and facilitators of adherence to medication among patients with HIV, such studies mostly relied on the quantitative designs that fail to adequately explain the ecological factors influencing the adherence.…”
Section: Introductionmentioning
confidence: 99%